Bent-core mesogens with an aromatic unit at the terminal position. (18th May 2017) - Bajzíková, Kvetoslava; Svoboda, Jiří; Novotná, Vladimíra; Pociecha, Damian; Gorecka, Ewa
Abstract : Bent-core liquid crystals with a naphthalene central unit and an aromatic ring at the terminal position of molecular chains were synthesised with the aim of enhancing nanosegregation. Abstract : Bent-core liquid crystals with a naphthalene central unit and an aromatic ring at the terminal position of molecular tails were synthesised with the aim of enhancing nanosegregation. It was found that the length of the spacer between the rigid core and the terminal aromatic moiety had a profound influence on the liquid crystal polymorphism. The homologues with short spacers exhibited nematic and columnar phases, whereas the homologue with long spacers exhibited a tilted lamellar phase with a liquid-like in-plane order, indicating an unusual morphology of the densely packed toroidal objects. The morphology can be changed to twisted ribbons by small additives adsorbed on the membrane surface. This is the first example of twisted ribbons constructed by a lamellar system with no long-range in-plane order.